(untitled) (The Conference Hub, 2025)
This thesis examines the factors affecting the success of dental implantation in patients with bone deficiency. Atrophy or resorption of the alveolar bone reduces primary implant stability and slows osteointegration. In modern clinical practice, bone augmentation, sinus lift, PRF (Platelet-Rich Fibrin), and bioactive materials are effectively used to address this issue. Studies show that using such regenerative methods can increase the success rate of implantation to 90–95%.